Seymour Glass: Contextual and Linguistic Identity - Kulchytska, O.; Baloh, E. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
In the article, the personality of Seymour Glass, the chief character of the Glass family saga by J.D. Salinger, is analyzed from social and his own philosophical perspectives. Two of Salinger’s works – ‚A Perfect Day for Bananafish‛ and ‚Hapworth 16, 1924‛, which complement each other in terms of character analysis, – are the focus of our attention. They offer answers to the questions (a) how the personality of Seymour predetermines the frame structure of the whole Glass series, (b) why Salinger starts with the end of Seymour’s life and ends with its beginning, and (c) what are the author’s motives in writing ‚Hapworth‛ since one of its central ideas – philosophy of reincarnation – has already been presented in ‚Teddy‛.